1984
DOI: 10.1364/josaa.1.000893
|View full text |Cite
|
Sign up to set email alerts
|

Perceived velocity of moving chromatic gratings

Abstract: Equiluminous red-green sine-wave gratings were drifted at a uniform rate in the bottom half of a 10-deg field. In the top half of the display was a sinusoidal-luminance grating of the same spatial frequency and 95% contrast that drifted in the opposite direction. Observers, while fixating a point in the display center, adjusted the speed of this upper comparison grating so that it appeared to match the velocity of the chromatic grating below. At low spatial frequencies, equiluminous gratings were appreciably s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
160
1
2

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(180 citation statements)
references
References 13 publications
13
160
1
2
Order By: Relevance
“…The same advantage held for color discrimination when the stimuli were displayed in the fovea, ensuring that this result was not based on potential luminance artifacts. This result is surprising because pursuit initiation relies on visual motion processing, and color and motion were treated as being independent for a long time (e.g., Cavanagh, Tyler, & Favreau, 1984;Ramachandran & Gregory, 1978). Newer work shows that chromatic motion can be seen, even though it is processed differently (Gegenfurtner & Hawken, 1996), presumably by a mechanism tuned to slow speeds, and mediated by attention (Cavanagh, 1992;Lu & Sperling, 1995).…”
Section: Visual Sensitivity During Pursuitmentioning
confidence: 99%
“…The same advantage held for color discrimination when the stimuli were displayed in the fovea, ensuring that this result was not based on potential luminance artifacts. This result is surprising because pursuit initiation relies on visual motion processing, and color and motion were treated as being independent for a long time (e.g., Cavanagh, Tyler, & Favreau, 1984;Ramachandran & Gregory, 1978). Newer work shows that chromatic motion can be seen, even though it is processed differently (Gegenfurtner & Hawken, 1996), presumably by a mechanism tuned to slow speeds, and mediated by attention (Cavanagh, 1992;Lu & Sperling, 1995).…”
Section: Visual Sensitivity During Pursuitmentioning
confidence: 99%
“…Much of the debate has been based on subjective observations about the appearance of motion in such patterns (Cavanagh & Anstis, 1991;Cavanagh, Tyler & Favreau, 1984;Krauskopf & Farell, 1990;Ramachandran & Gregory, 1978), and about perceptual aftereffects (Derrington & Badcock, 1985a;Mullen & Baker, 1985). However the issues have also been addressed using psychophysical discrimination measurements (Lindsey 8z Teller, 1990;Troscianko & Fahle, 1988).…”
Section: Contribution Of Chromatic Mechanisms To Motion Sensitivitymentioning
confidence: 99%
“…Ramachandran and Gregory (1978) concluded that "colour and motion are handled separately by the human visual system and that colour provides only a weak "cue" at best to motion perception". More recently it has been shown that moving colour patterns elicit percepts very similar to those elicited by moving luminance patterns, although the impression of motion they elicit may not be so robust: the apparent speed of moving colour gratings is lower than that of luminance gratings (Cavanagh et al, 1984), even to the point that adding colour to a luminance grating reduces its apparent speed of motion. However, prolonged viewing of equiIuminant coloured gratings induces a normal motion-after-effect (MAE) in the form of an impression of motion in the opposite direction to that of the pattern with has been viewed (Cavanagh & Favreau, 1985;Derrington & Badcock, 1985a;Mullen & Baker, 1985).…”
Section: Contribution Of Chromatic Mechanisms To Motion Sensitivitymentioning
confidence: 99%
“…Parameters of motion standstill. Motion standstill has been observed in isoluminant color motion (1)(2)(3)(4)(5)(6)(7)(8), stroboscopic motion (9-15), motion adaptation (16)(17)(18)(19)(20), and stereo motion (21). The temporal frequency range in which motion standstill is most frequently reported is Ͻ6 Hz, well within the range in which motion is easily detected.…”
mentioning
confidence: 92%